PENGENALAN PUBLIC SPEAKING DI ERA DIGITAL - Yopy Ratna Dewanti; Setiawan Setiawan; Herry Syafrial; Minggu Minggu; Umi Hanik Makmurah (POLITEKNIK LP3I JAKARTA, 2026)
Technological advancements have transformed public speaking. Speakers are now required not only to be able to speak well face-to-face but also to understand the use of digital communication technologies. For example, the use of cameras, microphones, visual presentations, and the ability to maintain audience interaction online. These benefits include increased self-confidence, facilitating the delivery of ideas and information, supporting careers and professionalism, enhancing interpersonal communication skills, and helping build personal branding in digital media. To be a good speaker in the digital era, one needs to pay attention to several important aspects, such as: mastery of material, intonation and articulation, body language and expression, the use of engaging presentation media, and the ability to interact with audiences both online and offline. Furthermore, digital communication ethics are also crucial. Speakers must use polite language, respect the audience, avoid spreading false information, and maintain professionalism in every delivery. With the development of digital technology, public speaking skills have become one of the main soft skills needed in education, organizations, business, and the workplace. Therefore, every individual needs to continuously practice their public speaking skills to be able to adapt and communicate effectively in the digital era. In an era of globalization and increasingly fierce job competition, companies assess prospective employees not only on technical abilities (hard skills), but also on non-technical or soft skills such as communication, teamwork, leadership, and time management. This training is designed to improve the quality of human resources so they can adapt, collaborate, and contribute optimally in a professional work environment.